Proposed Criteria for Load and Resistance Factor Design - Galambos, Theodore V.; Ravindra, M.K. (Engineering Journal, 1978)
The previous paper by Pinkham and Hansell outlined the basis and the background for Load and Resistance Factor Design (LRFD) criteria for steel building structures. The present paper describes a document entitled Proposed Criteria for Load and Resistance Factor Design of Steel Building Structures. This document represents the end product of a research project conducted at the Civil Engineering Department of Washington University during the period 1969 through 1976. The project was sponsored by the Structural Steel and Steel Plate Producers Committees of the American Iron and Steel Institute, and it was guided by a Task Force chaired by Ivan M. Viest. The principal investigators were T. V. Galambos and M. K. Ravindra. The work involved the cooperation and help of many individuals and groups, and the proposed document, which is the subject of this paper, is the result of many iterations and trials. The design criteria have been tested in design office trials (see the paper by Wiesner, which follows in this issue).